An Analysis of the Use of Instagram among English Education Students at University of Mataram - Fitrianingsih, Fitrianingsih; Waluyo, Untung; Soepriyanti, Henny (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2024)
Instagram is being a popular platform among students nowadays. This demographic finds the platform engaging and useful for multiple purposes especially in language learning. This research study aimed to (a) find out how students of the English Education Program at the University of Mataram use Instagram for language learning, (b) to identify the motivation of the students in using Instagram for language learning, (c) to reveal the challenges faced by students in using Instagram as a learning tool. The research employed qualitative research method to provide a comprehensive understanding. Data were collected through questionnaire with 61 students in the third semester of English Education Program and interviewed ten students each of them. Among other findings, the present study reports the use, motivation, and challenge on using Instagram for language learning. Most students use Instagram to learn English by following English learning accounts; watching English content; learning from infographics and memes; reading captions; and etc. Their motivations include the desire for practical language application; the sense of community; and the convenience and entertainment value that Instagram offers. However, challenges such as potential distractions; the risk of encountering inaccurate information; and the need for self-discipline in a largely unstructured environment highlight the limitations of relying solely on this platform for language learning.